2006
DOI: 10.1016/j.cell.2005.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Activates Cleavage of CREBH to Induce a Systemic Inflammatory Response

Abstract: Regulated intramembrane proteolysis (RIP) of endoplasmic reticulum (ER) membrane-anchored transcription factors is known to maintain sterol homeostasis and to mediate the unfolded protein response (UPR). Here, we identified CREBH as a RIP-regulated liver-specific transcription factor that is cleaved upon ER stress and required to activate expression of acute phase response (APR) genes. Proinflammatory cytokines increase expression of ER membrane-anchored CREBH. In response to ER stress, CREBH is cleaved by sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
780
7
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 731 publications
(818 citation statements)
references
References 44 publications
23
780
7
8
Order By: Relevance
“…Because other UPR regulators controlled by mammalian Rip exhibit tissue-specific expression, e.g. OASIS in astrocytes (Kondo et al, 2005) and CREB-H in liver (Zhang et al, 2006), these results strongly suggest that ATF6 is indispensable to the induction of ER chaperones in response to ER stress. Furthermore, even if they were expressed in CHO cells, their contribution to the ERSE-mediated induction of ER chaperones would be marginal because CREB-H enhances UPR element-mediated transcription but not ERSE-mediated transcription (Zhang et al, 2006) and because OASIS prefers cAMP-response element to ERSE (Kondo et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Because other UPR regulators controlled by mammalian Rip exhibit tissue-specific expression, e.g. OASIS in astrocytes (Kondo et al, 2005) and CREB-H in liver (Zhang et al, 2006), these results strongly suggest that ATF6 is indispensable to the induction of ER chaperones in response to ER stress. Furthermore, even if they were expressed in CHO cells, their contribution to the ERSE-mediated induction of ER chaperones would be marginal because CREB-H enhances UPR element-mediated transcription but not ERSE-mediated transcription (Zhang et al, 2006) and because OASIS prefers cAMP-response element to ERSE (Kondo et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…SREBPs with a hairpin structure are responsible for cholesterol homeostasis . On the other hand, transmembrane proteins with type II topology, such as ATF6, OASIS (Kondo et al, 2005), and CREB-H (Zhang et al, 2006), are involved in the UPR where they maintain the homeostasis of the ER. Interestingly, these ER membrane-bound transcription factors are cleaved by the same two proteases localized in the Golgi apparatus, S1P and S2P, even though their activation is triggered by different stimuli .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CREBH is cleaved on ER stress and activates the expression of acute response genes [23]. A recent study showed that CREBH is nutritionally regulated [24].…”
Section: Introductionmentioning
confidence: 99%
“…Predictably, AIbZIP, one of OASIS family proteins, has a role in differentiation of sperms by two papers regarding its knockout mice (44,45). CREBH, another OASIS family member, has a role to activate expression of inflammatory response in the liver (13). Besides OASIS family proteins, canonical ER stress transducers have also been defined to play roles in development, differentiation, and maturation of the cells.…”
Section: Resultsmentioning
confidence: 99%